High pure zirconium - Pylypenko, M.M. (Вопросы атомной науки и техники, 2017)
The results of investigations of zirconium refining processes by methods of electron-beam melting and zone recrystallization using high-vacuum technology are presented. It is shown that the applied methods of zirconium refin-ing allow to effectively reduce the content of impurities. Investigation of the properties of the obtained samples of high-purity zirconium and the dependence of these properties on the content of impurities allowed to reveal new features of high-purity zirconium. Викладено результати досліджень процесів рафінування цирконію методами електронно-променевої плавки та зонної перекристалізації із застосуванням високовакуумної техніки. Показано, що ці методи рафі-нування цирконію дозволяють ефективно знизити вміст домішок. Дослідження властивостей отриманих зразків високочистого цирконію і залежності цих властивостей від вмісту домішок дозволили виявити нові особливості високочистого цирконію. Изложены результаты исследований процессов рафинирования циркония методами электронно-лучевой плавки и зонной перекристаллизации с применением высоковакуумной техники. Показано, что применяемые методы рафинирования циркония позволяют эффективно снизить содержание примесей. Исследования свойств полученных образцов высокочистого циркония и зависимости этих свойств от содержания примесей позволили выявить новые особенности высокочистого циркония.